2013
DOI: 10.12740/app/17496
|View full text |Cite
|
Sign up to set email alerts
|

When the Foundations of Life have been Upset…. An Integrated Clinical and Experimental Study with Refugees and Asylum Seekers

Abstract: SummaryAim Recent research results in clinical psychology, health psychology and neurobiology underline the relationship between dissociative states, complex posttraumatic syndromes and borderline functioning [11]. Our study is meant to investigate the traumatic hypothesis of borderline functioning and to develop appropriate psychotherapeutic measures based on artistic mediations. Material and Methods.To estimate the effect of traumatic events, from the beginning of life up to recent stressors, linked to natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…It was undertaken at the level of clinical subgroups of refugees [25] and of homeless and long-term unemployed people [26]. Statistical analyses showed that affective needs, longing and the feeling of vulnerability are expressed in the third person, whereas feelings of guilt, hatred and the description of conflictual relationships are expressed in the first person (on the conscious level).…”
Section: At the Level Of The Rotter Testmentioning
confidence: 99%
See 1 more Smart Citation
“…It was undertaken at the level of clinical subgroups of refugees [25] and of homeless and long-term unemployed people [26]. Statistical analyses showed that affective needs, longing and the feeling of vulnerability are expressed in the third person, whereas feelings of guilt, hatred and the description of conflictual relationships are expressed in the first person (on the conscious level).…”
Section: At the Level Of The Rotter Testmentioning
confidence: 99%
“…These factors are particularly prominent in people experiencing homelessness or drug addiction. The effect of external catastrophes and of suffering as an adult is seen more often in refugees [17,25,26].…”
Section: Synthesis Support For the Traumatogenic Hypothesis Of Bordermentioning
confidence: 99%